1997
DOI: 10.1002/(sici)1097-4644(19970915)66:4<433::aid-jcb2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an unusually high concentration of an ubiquitinated histone-like protein inTrypanosoma cruzi

Abstract: The conjugation of ubiquitin to histones H2A and H2B has been established in higher eukaryotes and has been related to changes in chromatin organization. In Trypanosoma cruzi, no condensation of chromatin occurs during mitosis. In order to determine the presence of histone ubiquitination in T. cruzi epimastigotes, histones were extracted from chromatin and analyzed by three electrophoretic systems: acid-urea, triton-acid-urea and sodium-dodecyl-sulphate polyacrylamide gel. The immunochemical detection of ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…This will be in line with other authors who postulate a strong contribution of post‐translational modifications of histone tails, such as acetylation phosphorylation, and ubiquitination in the modulation of chromatin structure and function [Li et al, 1993; Cheung et al, 2000]. In T. cruzi , Reverol et al [1997] have demonstrated the presence of an unusually high concentration of ubiquitinated histone‐like proteins.…”
Section: Discusionsupporting
confidence: 87%
See 2 more Smart Citations
“…This will be in line with other authors who postulate a strong contribution of post‐translational modifications of histone tails, such as acetylation phosphorylation, and ubiquitination in the modulation of chromatin structure and function [Li et al, 1993; Cheung et al, 2000]. In T. cruzi , Reverol et al [1997] have demonstrated the presence of an unusually high concentration of ubiquitinated histone‐like proteins.…”
Section: Discusionsupporting
confidence: 87%
“…Histone proteins of T.cruzi have been extensively characterized by Toro and co‐workers [Toro and Galanti, 1988, 1990; Toro et al, 1992, 1993] and Reverol et al [1997]. These authors characterized T.cruzi histones by their banding pattern in different gel systems, their solubility properties, and amino acid composition.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future directions that may hold particular relevance in this case should include a closer look at histone ubiquitination in trypanosomes. An unusually high concentration of a ubiquitinated histone‐like protein has been observed in T. cruzi (Reverol et al ., 1997). This may be significant as the ubiquitination of yeast H2B has been linked to telomere‐associated gene silencing (Sun and Allis, 2002).…”
Section: Histone Marks and Modifying Enzymesmentioning
confidence: 95%